Proceedings of the 2021 International Conference on Financial Management and Economic Transition (FMET 2021) 2021
DOI: 10.2991/aebmr.k.210917.017
|View full text |Cite
|
Sign up to set email alerts
|

Research on Fairness of IASB Conceptual Framework in Financial Reporting

Abstract: IASB conceptual framework acts as a practical tool and assistance when developing IFRS. By probing into the degree to which IASB conceptual framework meets the given definition of fairness, it can be concluded that with an adequate recognition of users and their requirements, conceptual framework generally satisfies the fairness mentioned despite some flaws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The authors concluded that IFRS for SMEs was crucial for NGOs to meet the high-quality standards set by the IASB. However, other studies found that complex local and international grant regimes confronted NGOs with different financial reporting requirements because their financial reporting practices by grant donors do not comply with the quality requirements set by the IASB (Mvunabandi, Lathleiff & Muzindutsi, 2022;Yiting, 2021). Thus, the NGO sector must improve its financial reporting practices and quality to satisfy diverse stakeholders' needs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that IFRS for SMEs was crucial for NGOs to meet the high-quality standards set by the IASB. However, other studies found that complex local and international grant regimes confronted NGOs with different financial reporting requirements because their financial reporting practices by grant donors do not comply with the quality requirements set by the IASB (Mvunabandi, Lathleiff & Muzindutsi, 2022;Yiting, 2021). Thus, the NGO sector must improve its financial reporting practices and quality to satisfy diverse stakeholders' needs.…”
Section: Introductionmentioning
confidence: 99%